Impact of periodic magnetic source on natural convection and entropy generation of ferrofluids in a baffled cavity. Issue 12 (4th March 2021) - Zontul, Harun; Hamzah, Hudhaifa; Sahin, Besir
Abstract : Purpose: This paper aims to exhibit a numerical study to analyze the influence of a periodic magnetic source on free convection flow and entropy generation of a ferrofluid in a baffled cavity. In this study, ferrofluid nanofluid was selected due to its ability to image magnetic domain structures within the cavity. The non-uniform magnetic source is considered as a sinusoidal distribution in the vertical direction. Design/methodology/approach: The finite volume technique is used to evaluate the steady two-dimensional partial differential equations that govern the flow with its corresponding boundary conditions. Findings: The obtained results indicate that a significant increase in the average Nusselt number can be achieved with the use of the periodic magnetic source instead of a uniform case. In addition, the effectiveness of the adiabatic baffle notably depends on its position and Rayleigh number. Regardless of the values of period and Hartmann numbers, the periodic magnetic source has a higher entropy generation and lower Bejan number than the uniform magnetic source. Originality/value: The novelty of this research lies in applying a periodic magnetic source on the natural convection of ferrofluids in a baffled cavity.